Impact of Health Marketing Mix on Competitive Advantage: The Case of King Hussein Cancer Center - Al-Taee, Hameed; Al-Khawaldeh, Khalid (Jordan Journal of Business Administration, 2020)
The main aim of this study is to investigate the impact of health marketing mix elements on the achievement of competitive advantage from the viewpoint of top - and middle - level management in King Hussein Cancer Center (KHCC) in Amman, the capital of the Hashemite Kingdom of Jordan. In order to achieve this fundamental objective, the researchers developed a theoretical framework based on relevant marketing literature. The proposed model includes four health marketing mix elements; namely, product (health service), price, integrated marketing communications and service providers and processes of health services).A questionnaire was designed for gathering primary data related to the independent variables of the health marketing mix, as well as the dependent variable represented in the competitive advantage. A total of 310 complete responses were received from employees representing the top -and middle- level management in KHCC, the process which was conducted in coordination with KHCC directors.The results of data analysis confirmed the impact of health marketing mix elements -as developed in the study`s theoretical framework- on competitive advantage variables. According to the values of (R2), the changes occurring in the four health marketing mix elements interpret a considerable amount of the changes in the competitive advantage of KHCC. In the forefront of these elements is price, the result that seems to be reasonable, because of the expected relationship between the price of provided health service and its perceived level of quality.In addition, the study suggested a number of recommendations. Most significantly is the attention that should be given for maintaining the unique competitive advantage that KHCC possesses, represented in the innovative way that health marketing mix elements are managed within an integrated system. Such system is intended to achieve mutual benefits for both parties: KHCC and the patients who benefit from cancer treatment. The study also recommended applying a pricing strategy that takes into account the financial capability of recipients of the health service provided by KHCC at both: the local and regional levels.